Área especial de interesse social: um estudo de caso no Assentamento Informal Urbano Nova Vida, Boa Vista - Roraima - Amazônia - Brasil - Ribeiro, Camila Mattos (2022)
Urbanization in cities and towns is accompanied by socio-spatial segregation and the emergence of urban informal settlements. Urban informal settlements are irregularly built housing places in public or vulnerable areas that lack essential public services. In Boa Vista, the Nova Vida Settlement is an expression of this phenomenon, as it was built on top of a sanitary landfill. To understand this phenomenon, the general objective of this study was to analyze the urbanization and settlement process in the Nova Vida Settlement, in the municipality of Boa Vista–RR and the aspects of socio-environmental vulnerability in the years of 2000 to 2020. The research design was presented by a case study based on Yin (2015), linked to the epistemological theoretical approach of the dialectic of complexity in Morin (2015). A quantitative-qualitative analysis of the data obtained through literature review and documental research was used, aligned with the environmental history apprehended in the field, involving participant observation, interviews, visits to public agencies and application of a form to residents. The sampling used the snowball method, through which key informants were found, and, when they did not present new information, the sample was saturated. The origin of the Nova Vida Settlement and its relation and interactions represent the complexity of this system. The movements undertaken by the organizations legitimized the settlement as a Special Area of Social Interest, transforming the place that was previously destined for the disposal of waste into a place of residence, a contradictory dynamic because, at the same time it follows the guidelines imposed by the Strategic and Participatory Master Plan of Boa Vista, it also violates the right to human dignity. The data on display, with theoretical references, revealed that the informal occupation of the area is a result of a historical process of urbanization in the capital, which shows traces of socio-spatial segregation and inequalities. In the case of a deactivated sanitary landfill, the results revealed that the infrastructure and sanitation are inadequate, and the residents had difficulties in accessing public policies. Aligned with this set of circumstances, there is still a process of environmental degradation, since the houses were built on the banks of the Igarapé Grande.